Interlink between solubility, structure, surface and thermodynamics in the ThO2(s, hyd)–H2O(l) system - Kiefer, Christian; Neill, Thomas; Cevirim-Papaioannou, Nese; Schild, Dieter; Gaona, Xavier; Vitova, Tonya; Dardenne, Kathy; Rothe, Jörg; Altmaier, Marcus; Geckeis, Horst (Frontiers in Chemistry, 2022)
The impact of temperature on a freshly precipitated ThO2(am, hyd) solid phase was investigated using a combination of undersaturation solubility experiments and a multi-method approach for the characterization of the solid phase. XRD and EXAFS confirm that ageing of ThO2(am, hyd) at T = 80°C promotes a significant increase of the particle size and crystallinity. TG-DTA and XPS support that the ageing process is accompanied by an important decrease in the number of hydration waters/hydroxide groups in the original amorphous Th(IV) hydrous oxide. However, while clear differences between the structure of freshly precipitated ThO2(am, hyd) and aged samples were observed, the characterization methods used in this work are unable to resolve clear differences between solid phases aged for different time periods or at different pH values. Solubility experiments conducted at T = 22°C with fresh and aged Th(IV) solid phases show a systematic decrease in the solubility of the solid phases aged at T = 80°C. In contrast to the observations gained by solid phase characterization, the ageing time and ageing pH significantly affect the solubility measured at T = 22°C. These observations can be consistently explained considering a solubility control by the outermost surface of the ThO2(s, hyd) solid, which cannot be properly probed by any of the techniques considered in this work. Solubility data are used to derive the thermodynamic properties (log *K°s,0, ΔfG°m) of the investigated solid phases, and discussed in terms of particle size using the Schindler equation. These results provide new insights on the interlink between solubility, structure, surface and thermodynamics in the ThO2(s, hyd)–H2O(l) system, with special emphasis on the transformation of the amorphous hydrous/hydroxide solid phases into the thermodynamically stable crystalline oxides.